Cellular immune responses to HCV core increase and HCV RNA levels decrease during successful antiretroviral therapy. Issue 9 (26th July 2010) - Rohrbach, Janine; Robinson, Nicola; Harcourt, Gillian; Hammond, Emma; Gaudieri, Silvana; Gorgievski, Meri; Telenti, Amalio; Keiser, Olivia; Günthard, Huldrych F; Hirschel, Bernhard; Hoffmann, Matthias; Bernasconi, Enos; et al.
Abstract : Background: Hepatitis C virus (HCV) infection is a major cause of morbidity in HIV infected individuals. Coinfection with HIV is associated with diminished HCV-specific immune responses and higher HCV RNA levels. Aims: To investigate whether long-term combination antiretroviral therapy (cART) restores HCV-specific T cell responses and improves the control of HCV replication. Methods: T cell responses were evaluated longitudinally in 80 HIV/HCV coinfected individuals by ex vivo interferon-γ-ELISpot responses to HCV core peptides, that predominantly stimulate CD4 + T cells. HCV RNA levels were assessed by real-time PCR in 114 individuals. Results: The proportion of individuals with detectable T cell responses to HCV core peptides was 19% before starting cART, 24% in the first year on cART and increased significantly to 45% and 49% after 33 and 70 months on cART (p=0.001). HCV-specific immune responses increased in individuals with chronic (+31%) and spontaneously cleared HCV infection (+30%). Median HCV RNA levels before starting cART were 6.5 log10 IU/ml. During long-term cART, median HCV-RNA levels slightly decreased compared to pre-cART levels (−0.3 log10 IU/ml, p=0.02). Conclusions: Successful cART is associated with increasing cellular immune responses to HCV core peptides and with a slight long-term decrease in HCV RNA levels. These findings are in line with the favourable clinical effects of cART on the natural history of hepatitis C and with the current recommendation to start cART earlier in HCV/HIV coinfected individuals.